Enhancement of Avermectin Water-solubility by Addition of Poloxamer 188 and Deep Eutectic Solvent into PEG 6000 Solid Dispersion System - He, Xue-Hua; Chen, Meng; Pu, Yang; Huang, Xing-Zhou; Han, He; Jin, Zhi-Min (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: It has been reported previously that AV water-solubility was enhanced great by solid dispersion in PEG6k carrier. Materials and Methods: In this study, AV water-solubility was improved primarily by addition of PLX188 into PEG6k carrier, and further by addition of a deep eutectic solvent of CBU (choline chloride, betaine and urea) in the combinatory carrier of PEG6k and PLX188. Results: The result showed that the water-solubility of AV-PEG6k-PLX188 solid dispersion was 10.8 times of AV-PEG6k solid dispersion, and the cumulative dissolution rate (within 60 min) of AV-PEG6k-PLX188 solid dispersion was 3.3 times of AV-PEG6k solid dispersions. With the further addition of CBU in the AV-PEG6k-PLX188 system, the water-solubility of AV-PEG6k-PLX188-CBU solid dispersion was increased by 3.4 times, and the cumulative dissolution rate (within 60 min) was increased by 1.6 times. The X-ray powder diffraction measurement indicated that AV existed in the AV-PEG6k-PLX188-CBU solid dispersion as a non-crystalline state. Further, the in vitro toxicity against 3rd instar Asiatic migratory locust was measured, which showed that the LC50 of the AV-PEG6k-PLX188-CBU solid dispersion (0.88 mg/L) was a third of that of AV emulsifiable concentrate (2.64 mg/L), suggesting a higher bioavailability. Conclusion: The finding of this work showed that AV-PEG6k-PLX188-CBU solid dispersion was more effective than AV emulsifiable concentrate, in suppressing or killing locusts.
Keywords: Solid dispersion; Avermectin; Water-solubility; Stability; Bioavailability